Research on Effects of Internal Marketing: A Review - Bich Hanh Tran, Thi; ., . (International Journal of Engineering and Technology, 2018)
With the increased competition in the temporary economy, organizations increasingly strive for progressive practices to achieve organizational goals. Internal marketing – treating employees as customers – has recently been suggested as an effective approach to reach positive organizational outcomes. Though research of internal marketing recently increased dramatically, a large number of the studies are case studies and lack strong theoretical backgrounds. A review of internal marketing research is valuable for future research to gain an insight of the research streams of internal marketing and so identifying the compelling areas to pursue. This review attempts to analyze the research of internal marketing and suggest potential directions for future research.